Museu e suas tipologias: o webmuseu em destaque - Santos, Plácida Leopoldina Ventura Amorim da Costa [UNESP]; Lima, Fábio Rogério Batista [UNESP] (Universidade Federal de Campina Grande, 2014)
The rapid development of Information and Communication Technologies - TIC, coupled with the advancement of the global Internet computer network have framed new concepts and definitions such as virtual reality, immersive environments, webmuseums, digital museums, electronic art, cyber art, among other terminologies that are becoming more and more common and are present in everyday Web users. To better understand the terminologies used to describe museum in the virtual environment, we present a summarized table of terms such as webmuseum, virtual museum, digital museum and their derivatives in order to define the elements that differentiate or resemble them. We used the bibliographic descriptive method for identifying the concepts presented by some expert authors in the field. In conclusion, we recommend the use of the term webmuseum for museums in cyberspace as the most appropriate and we define the concept, comprehending its meaning and characteristics.

O acelerado desenvolvimento das Tecnologias da Informação e Comunicação – TIC, somado ao avanço da rede mundial de computadores Internet, fez surgir conceitos e definições como realidade virtual, ambientes imersivos, webmuseus, museus digitais, arte eletrônica, ciberarte, dentre outros termos que são cada vez mais comuns e estão presentes no cotidiano dos usuários da Web. Na perspectiva de entender melhor as terminologias utilizadas para designar museu no ambiente virtual, apresenta-se um quadro síntese de termos como webmuseu, museu virtual, museu digital e seus derivados no intuito de definir os elementos que os diferenciam e os que se assemelham. Utilizou-se o método bibliográfico descritivo, para a identificação dos conceitos apresentados por alguns autores especialistas da área. Como conclusão, recomenda-se a utilização do termo webmuseu para museus no ciberespaço como sendo o mais apropriado e aponta-se o seu conceito, abrangendo significado e características.
Museum and its types: the webmuseu featured
Keywords: Museum; Webmuseum; Types of museum's websites; Museu; Webmuseu; Tipologias de sites de museu